Legal Consequences For Neglected Land Holders Right Based On Government Regulation Number 11 Of 2010 - Samiyah, Firza; Arwanto, Bambang (Green Publisher, 2022)
A neglected land is a plot of land that is purposely not utilized as allotment by the landholder. It is done in a certain period and causes consequences for people who are in the location land displaced be. What makes neglecting land become a wrong action is because it will arouse negative impact if it is handled wrongly. The aims of this research is to explore the legal consequnces for neglected land holdres right based on government regulation number 11 of 2010. This is a normative law study, the researcher use legislation and library studies to collect the data. The reslts shows that to prevent the negative effect occurrence, land neglectment should be anticipated earlier. Hence, the Regulation of agrarian principles Number 15 of 1960 reminds everyone, especially the landholder, to not abandon the land purposely. The seriousness of the BAL prohibits the existence of neglecting land, looks at the threat in the form of sanctions that will be given, that is delete it right on the land in question, termination connection law between the land and the owner, and the land will be confirmed as State Land.